Place, Time and Doing the Right Thing: The Moral Geographies of Adult Education - Thomas J. Sork (Adult Education Research Conference, 2002)
This study explores the relationships between the spatial-temporal locations of adult education faculty during key points in their development and the moral imperatives and ethical frameworks that inform their teaching in graduate programs around the world.